Fraudulent financial reporting : an application of fraud models to Malaysian public listed companies - Mohamed Yusof, Khairusany (2016)
There have been great concerns among stakeholders on how fraudulent financial reporting (FFR) can affect the reputation of public-listed companies (PLCs). The post Enron era has witnessed many FFR cases around the globe. FFR has impacted many countries around the world including Malaysia, the focus of this thesis. FFR not only causes significant ethical concerns to both individuals and companies but also involves a great amount of financial losses. A survey conducted by KPMG (2014) involving Chief Executives in Malaysian PLCs between January 2010 and December 2013 has found that 26% of respondents who experienced fraud were able to state the estimate of fraud losses experienced, which amounted to RM 2.41 million (≈ USD 0.72 million) on average. Thus, FFR is a major concern for the two primary regulators of the capital markets in Malaysia; Bursa Malaysia and Securities Commission Malaysia (SC). Both authorities continue to refine the parameters that help to ensure rigorous surveillance over Malaysian PLCs (Danial et al, 2014). Effective anti-fraud programmes which include the ability to predict the likelihood of FFR among Malaysian PLCs continue to be important not only for regulators, but also to the nation. Therefore, this research examines suitable determinants of the likelihood of FFR among Malaysian PLCs based on the fraud-risk factors identified in the Fraud Models [i.e. Fraud Triangle Model (Cressey, 1953), the Fraud Diamond Model (Wolfe & Hermanson, 2004) and Crowe’s Fraud Pentagon Model (Crowe, 2011)]. Based on previous literature on FFR and the Fraud Models, this research has identified five predeveloped hypotheses and ten pre-developed sub-hypotheses. Semi-structured interviews were undertaken to explore relevant fraud-risk factors from these predeveloped hypotheses and sub-hypotheses in the Malaysian context. Additionally, interview results have also suggested measurable fraud-risk factors as Malaysian specific results, which have not been tested before. These factors are ignorance and greed. Then, these factors were statistically tested in quantitative analyses (i.e. descriptive statistics and binomial logistic regression analysis). Utilising crosssectional data series, which involve 160 Malaysian PLCs (45 fraudulent PLCs and 115 non-fraudulent PLCs) for a 10-year period (from 2004 to 2013), this research examines sixteen proxy variables on seven hypotheses and fourteen sub-hypotheses. Ultimately, based on panel data models of binomial logistic regression analysis, this research has found a new fraud model with suitable fraud-risk factors that could fit current business environment and corporate governance culture in Malaysia. In short, utilising a mixed-method design, this research has explored a new perspective in suggesting suitable fraud-risk factors to predict the likelihood of FFR among Malaysian PLCs.
HydraID: hull:14393 Hydra Discover Access Group: public ETD Collection: ETDBusinessSchool
Keywords: Business